DETERMINANTS OF COMPLIANCE IN PAYING TAXES: TAX UNDERSTANDING AND TAX AWARENESS AS INTERVENING VARIABLES: DETERMINANTS OF COMPLIANCE IN PAYING TAXES: TAX UNDERSTANDING AND TAX AWARENESS AS INTERVENING VARIABLES - Apni, Riza Nur; Supeno, Bambang; Burhan , Burhan (PENANOMICS: International Journal of Economics, 2024)
Tax is a source of state revenue used to finance development and public services. Tax collection success is highly dependent on taxpayer compliance in carrying out their tax obligations. However, the level of tax compliance in various countries, including Indonesia, is still a significant challenge for the government. This is due to multiple factors, including tax compliance, tax understanding and taxpayer awareness. This study aims to analyze the effect of tax understanding on taxpayer awareness of motor vehicles, tax understanding of paying motor taxes, taxpayer awareness of paying motor taxes, and taxpayer awareness in mediating tax understanding of paying motor taxes. The research method is quantitative with descriptive explanation, a sample of 196 taxpayers, and data processing using SEM PLS. The research findings show that 1) tax understanding has a positive effect on the awareness of  taxpayers’ motor vehicles, 2) tax understanding has a positive effect on compliance in paying  taxes motor vehicles, 3) taxpayer awareness has an effect on compliance in paying  taxes motor vehicle, 4) taxpayer awareness mediates tax understanding in influencing compliance in paying taxes motor vehicle at the Rengat Revenue Management UPT.